Mental Development of Preschool Children - Maxkambayeva Shaxrizoda Xusan qizi; Binoqulova Dilnora Sirojiddin qizi (Global Scientific Publishing, 2022)
This article describes the methods, problems and solutions of mental development of children of preschool age in the preschool education system
Keywords: perception; mind; consciousness; thinking